Stable isotope ecology of modern herbivores from Mmabolela, Limpopo - Lethuba, Malefeu (Department of Archaeology, 2024)
This thesis explores the stable isotope ecology of 12 species of co-existing wild herbivores (11 mammals and one reptile) (62 individuals) from Mmabolela, a game farm on the northern border of South Africa in the Limpopo Province. The aim is to investigate and interpret patterns in δ13C, δ15N and δ18O values of different species of herbivores and to compare these results with previous studies. As expected in this summer-rainfall region, δ 13Cbone collagen values fall into two distinct groups: predominant browsers with mean δ13C values ranging from -21.37‰ to -18.10‰, and grazing species with mean δ13C values ranging from -13.25‰ to -10.49‰, the more negative values reflecting some supplementary feeding with lucerne during the dry season. There are no differences in δ13C between the browsing species eland (Taurotragus oryx), bushbuck (Tragelaphus scriptus) and kudu (Tragelaphus strepsiceros). The δ 15N values for all species (including corrected values for keratin from Hystrix africaeaustralis) range from 7.73‰ to 11.20‰. δ 15N values of baboons fall within the range seen in bovids. Amongst bovids, there is no statistically significant difference between the δ15N values of browsers (drought-tolerant or water-independent) and grazers (obligate drinkers). Zebra have lower δ15N values. The potential of porcupine quills to provide a record of seasonal dietary changes was investigated by serial sampling of quills from three porcupines (Hystrix africaeaustralis), and tooth enamel from nine zebra (Equus quagga). The porcupines show short-term, but not necessarily seasonal variations in their diets. δ 13C and δ18O profiles of the second and third molars of nine Equus quagga individuals are highly variable. A better understanding of the isotopic ecology of communities such as this will help to interpret similar analyses of fossil faunal assemblages and assist in reconstructing palaeoenvironments.